2004
DOI: 10.1115/1.1683663
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement Using Shaped Polymer Tubes: Fin Analysis

Abstract: The use of polymer tubes for heat exchanger tube bundles is of interest in many applications where corrosion, mineral build-up and/or weight are important. The challenge of overcoming the low thermal conductivity of polymers may be met by using many small-diameter, thin-walled polymer tubes and this route is being pursued by industry. We propose the use of unique shaped tubes that are easily extruded using polymeric materials. The shaped tubes are streamlined to reduce form drag yet the inside flow passage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In order to reduce the conductive resistance of the polymer wall and maintain acceptable pressure drops, researchers have focused on the efforts to develop polymer tube bundles with small diameter and thin wall tubes. The fluid dynamic and thermal performance of using the unique shaped polymer tubes in bundles comprised of small diameter tubes (as shown in Figure 23) was conducted by Li et al 88 . The outer surface of the tube was streamlined into oval shapes to reduce form drag and the inner flow passage was kept circular to maintain pressure capability.…”
Section: Summary Of Heat Transfer Studies On Polymer Heat Exchanger 5mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the conductive resistance of the polymer wall and maintain acceptable pressure drops, researchers have focused on the efforts to develop polymer tube bundles with small diameter and thin wall tubes. The fluid dynamic and thermal performance of using the unique shaped polymer tubes in bundles comprised of small diameter tubes (as shown in Figure 23) was conducted by Li et al 88 . The outer surface of the tube was streamlined into oval shapes to reduce form drag and the inner flow passage was kept circular to maintain pressure capability.…”
Section: Summary Of Heat Transfer Studies On Polymer Heat Exchanger 5mentioning
confidence: 99%
“…The numerical analysis revealed that such geometry changes improved convective heat transfer with Re numbers in the range of 2000 to 20,000 and a Biot number less than 0.3. Figure 23 Tube bundle of 'shaped' polymer tubes 88 Park and Jacobi 89 proposed an analytical method to model the polymer heat exchanger tube bundle geometry. The tube core mass/ volume ratio, facial area ratios were tuned according to various heat transfer rate, pumping rate and pumping power.…”
Section: Summary Of Heat Transfer Studies On Polymer Heat Exchanger 5mentioning
confidence: 99%
“…Although finned tubes employing the third-generation heat transfer elements with various geometrical shapes have been exploited, few data related to their condensation or boiling heat transfer performances are seen [9,16]. Furthermore, studies on heat transfer performance of tubes that integrate multiple kinds of the third-generation heat transfer technologies are absent in open literature.…”
Section: Introductionmentioning
confidence: 97%
“…Polymers are large molecules made up from the repetition of subunits (monomers). In general, polymers have lower thermal stability and conductivity [1], problems with creeping, degradation, and lack of mechanical properties relative to metals. However, they have already been used as heat exchangers for many years due to benefits such as corrosion resistant, lightweight, low cost as compared to exotic metals, easy to manufacture, ability to handle both liquids and gases, and inherent resistance to fouling [2][3][4].…”
Section: Introductionmentioning
confidence: 99%